Cytokine profile in patients with atrophic gastritis in comorbidity with thyroid gland pathology - L.M. Mosiychuk; O.M. Tatarchuk; I.S. Konenko; O.P. Petishko (Gastroenterologìa, 2022)
Background. Optimization of the management of patients with precancerous conditions of the stomach in comorbid pathology is an urgent task of gastroenterology. The purpose of the study: to evaluate the content of pro- and anti-inflammatory cytokines, as well as the level of vascular endothelial growth factor (VEGF) at different degrees of vascularization of the thyroid gland in patients with atrophic gastritis. Materials and methods. A study was conducted in 120 patients with atrophic gastritis and thyroid pathology. All of them underwent a sonological examination of the thyroid gland using an ultrasound scanner Toshiba Xario (Japan), which revealed poor vascularization of the parenchyma in 82 (68.3 %) cases, moderate vascularization was diagnosed in 20 (16.7 %) patients and marked — in 18 (15.0 %). Quantitative content of cytokines (interleukins (IL) 8, 10, 18, tumor necrosis factor α), vascular endothelial growth factor in the blood serum was determined by immunoenzymatic assay using Vector-Best reagents. Results. Among patients with poor vascularization, only atrophic changes of the gastric mucosa were diagnosed in almost half — 39 (47.6 %) people, while dysplastic changes of the gastric mucosa were found in a third of patients with marked vascularization. Intestinal metaplasia was detected in half of cases, regardless of the degree of vascularization of the thyroid parenchyma. Cytokine imbalance was found in patients with atrophic gastritis, with the greatest shift in case of marked vascularization of the thyroid parenchyma due to a 4-fold increase in the level of pro-inflammatory cytokines IL-8 (р < 0.05) and by 1.7 times of IL-18 (p < 0.05), with a simultaneous decrease in the content of the anti-inflammatory cytokine IL-10 by 3.2 times (p < 0.05) compared to control indicators. The level of VEGF in the blood serum of patients with atrophic gastritis with moderate and marked vascularization of the thyroid parenchyma was significantly increased by 1.5 (p < 0.05) and 1.7 times (p < 0.05), respectively, compared to that of people with poor vascularization. Correlations were revealed between the degree of vascularization of the thyroid parenchyma and the level of IL-8 (r = 0.491; p = 0.031) and VEGF (r = 0.444; p = 0.019) in patients with atrophic gastritis. Conclusions. Patients with atrophic gastritis had a cytokine imbalance, which deepens as the vascularization of the thyroid gland increases that is possibly related to common pathogenetic mechanisms of the development of comorbid pathology.